2016
DOI: 10.1103/physrevd.93.042002
|View full text |Cite
|
Sign up to set email alerts
|

Observing gravitational waves from core-collapse supernovae in the advanced detector era

Abstract: The next galactic core-collapse supernova (CCSN) has already exploded, and its electromagnetic (EM) waves, neutrinos, and gravitational waves (GWs) may arrive at any moment. We present an extensive study on the potential sensitivity of prospective detection scenarios for GWs from CCSNe within 5 Mpc, using realistic noise at the predicted sensitivity of the Advanced LIGO and Advanced Virgo detectors for 2015, 2017, and 2019. We quantify the detectability of GWs from CCSNe within the Milky Way and Large Magellan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
118
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(126 citation statements)
references
References 172 publications
7
118
1
Order By: Relevance
“…We use the observational data taken by H1 and L1 during the S5 science run, and data taken by V1 during the VSR1 science run, which is now publicly available via the LIGO Open Science Center (LOSC) [82]. This data is recolored to the design sensitivity Power Spectral Density (PSD) of aLIGO and AdVirgo, as outlined in [14], which permits a more realistic estimation of the sensitivity of our analysis in future advanced detector observation runs. The detectors are expected to reach design sensitivity in 2019.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We use the observational data taken by H1 and L1 during the S5 science run, and data taken by V1 during the VSR1 science run, which is now publicly available via the LIGO Open Science Center (LOSC) [82]. This data is recolored to the design sensitivity Power Spectral Density (PSD) of aLIGO and AdVirgo, as outlined in [14], which permits a more realistic estimation of the sensitivity of our analysis in future advanced detector observation runs. The detectors are expected to reach design sensitivity in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…AdVirgo is a 3km Italian detector expected to join the aLIGO detector network early in 2017 [13]. Recent work by Gossan et al [14] shows that GWs from non-rotating and rotating core collapse may be observable throughout the Milky Way and the Large Magellanic Cloud (LMC). The rate for these sources is low at around 2 − 3 CCSNe per 100yr [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each waveform, we give the emission type, journal reference, waveform identifier, angle-averaged root-sum-squared strain hrss, the frequency f peak at which the GW energy spectrum peaks, the emitted GW energy EGW, and available polarizations. See [73,142] Note that since the simulation producing this waveform was axisymmetric, only the + polarization is available.…”
Section: Waveforms From Multi-dimensional Ccsn Simulationsmentioning
confidence: 99%
“…Previous targeted GW searches have been carried out for gamma-ray bursts [62][63][64][65][66][67][68][69], softgamma repeater flares [70,71], and pulsar glitches [72]. A recent study [73] confirmed that targeted searches with Advanced LIGO and Virgo at design sensitivity should be able to detect neutrino-driven CCSNe out to several kiloparsecs and rapidly rotating CCSNe out to tens of kiloparsecs, while more extreme GW emission scenarios will be detectable to several megaparsecs. An extended analysis [74] of GW spectrograms show that several characteristic CCSN signal features can be extracted with KAGRA, Advanced LIGO and Virgo network.…”
Section: Introductionmentioning
confidence: 99%